Hydrothermally stable ZnAl2O4 nanocrystals with controlled surface structures for the design of long-lasting and highly active/selective PdZn catalysts. Issue 24 (14th November 2019) - Zhang, Xian-Hua; Liu, Chang; Ke, Congming; Liu, Liang; Hao, Xinning; Wu, Yaping; Wan, Shaolong; Wang, Shuai; Wang, Yong
Abstract : Synthesis of hydrothermally stable ZnAl2 O4 nanocrystals with controlled surface structures and the design of long-lasting and highly active/selective PdZn catalysts. Abstract : Hydrothermally stable ZnAl2 O4 nanocrystals with controlled surfaces including Zn-rich and Al-rich structures are synthesized by a facile method. The Zn-rich surfaces are utilized to design long-lasting PdZn/ZnAl2 O4 catalysts evaluated in the aqueous phase hydrogenolysis of glycerol for 10 consecutive cycles showing high activity and selectivity.